(untitled) (Global Journals of Research in Engineering, 2024)
This study utilized the Aspen HYSYS Simulator Version 8 6 to simulate plant operations and optimize natural gas recovery using Technip s feed gas composition The focus was on investigating the effects of product recycling and determining the optimal feed tray position within the distillation column Technip s feed gas composition was selected due to its relevance in real-world applications influencing the efficiency of methane recovery The results indicated that maximum methane recovery occurred with zero product recycling and increasing the number of trays significantly enhanced methane recovery in the column overhead Specifically the analysis revealed a direct correlation between the number of trays and methane recovery efficiency To support these findings mathematical models were developed one for predicting the optimal feed tray position represented as y 0 01x2 x 3y 0 01x2 x 3 and two models for calculating the required number of trays for desired fractions of methane and natural gas liquids NGLs in the overhead These models are expressed as y 2E 06x2 3E 05x 0 8931y 2E 06x2 3E 05x 0 8931 for methane and y 5E 07x2 5E 05x 0 0352y 5E 07x2 5E 05x 0 0352 for NGLs The accuracy and reliability of these models were validated through simulation results In conclusion this study demonstrates that optimizing tray configurations and minimizing product recycling can significantly enhance methane recovery processes The developed models provide valuable tools for engineers and industry practitioners aiming to improve natural gas recovery efficiency in operational settings